MOTIVASI, PEMAHAMAN AKUNTANSI DAN MINAT MAHASISWA UNTUK MENGIKUTI SERTIFIKASI AKUNTAN PROFESIONAL - Franciska Diva Setiani; Maria Rio Rita (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
Professional accountant certification is one way that accounting students can later be recognized as professional accountants. Unfortunately, not all accounting students are interested in joining professional accountant certification. This study aims to determine whether economic motivation, degree motivation, quality motivation and understanding of accounting affect the interest of accounting students to take professional accountant certification. In this study uses primary datahad no, which were obtained through questionnaires distributed directly and also through student e-mails to the accounting students at Satya Wacana Christian University (SWCU). This research uses purposive sampling. The data analysis technique used is binary logistic regression analysis. The results showed that degree motivation effect the interest of accounting students to take professional accountant certification. Meanwhile, economic motivation, quality motivation and understanding of accounting do not effect on interest of accounting students to take professional accountant certification.Keyword(s):  Professional accountant certification, Economic motivation, Degree motivation, Quality motivation, Understanding of accounting